A Long-Term Survivor with Tetralogy of Fallot Treated Only with the Classical Blalock-Taussig Shunt. (19th August 2018) - Yamada, Yu; Ishizu, Tomoko; Tsuneoka, Hidekazu; Eki, Yutaka; Horigome, Hitoshi
Abstract : The prognosis of tetralogy of Fallot (TOF) treated only with Blalock-Taussig shunt (BTS) operation is unclear. A woman with TOF underwent classic BTS operation at 10 years of age. Despite no medication, she delivered two children and worked without apparent heart failure. At 72 years of age, she complained of dyspnea on exertion and leg edema. The cardiac angiogram revealed a well-patent BTS and severely stenotic right ventricular outflow tract. Right heart catheterization showed adequately maintained pulmonary blood flow with slight pulmonary arterial hypertension. Her unexpected yet favorable outcome reaffirms the importance of structural and functional self-adaptation even with cyanosis. If she had undergone a valve-sparing corrective surgery in adolescence, much better quality of life and outcome could have been expected.